(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article discusses different views of linguists on borrowings in modern Russian, analyzes different types of borrowings. The strengthening of the processes of globalization and digitalization of modern life leads to the fact that borrowings, as a rule, from other languages, actively penetrate into many languages, including Russian. With the advent of new life realities, there is a need for their concise nomination, which the lexical system of the Russian language cannot always provide. A negative consequence is the clogging of the Russian language, which is expressed in the inappropriate use of foreign vocabulary. Borrowed words that are most actively used in modern Russian can be conditionally combined into the following thematic groups: "Information technology", "Economy", "Politics", "Science", "Culture", "Social and psychological phenomena", "Fashion and beauty”, “Sport”, “Gastronomy”.